They speak what language to whom?!: Acculturation and language use for communicative domains in bilinguals. (September 2017) - Hammer, Kate
Abstract: This paper investigates the extent of second language (L2) use across four communicative domains in 149 highly educated L2-competent sequential Polish-English bilinguals resident in the UK. 1 The domains under investigation include: work, household, interest group, and peer group. Work and interest group count as public domains, while household and peer group count as private domains. The independent variables include acculturation level, social network profile, predicted future domicile, and length of residence. The instruments include an online questionnaire and semi-structured interviews. The results show that bilinguals who acculturate to a higher level use the L2 more frequently, even in private domains. The findings also suggest that bilinguals who operate in majority L2-speaking social networks, use the L2 more frequently during informal conversations with other L1-speakers at work. Highlights: Acculturation linked to the extent of L2 use in all domains apart from work. Social network linked to the extent of L2 use during informal conversations at work. Extent of L2 use in private domains found to be linked to acculturation level. Language use for communicative domains indicative of being a reliable acculturation marker.